(untitled) (Philological Studies, 2019)
Imageability has been argued to induce asymmetry in processing of nominal lexical units as this feature of the mental lexicon is sensitive to the organization of the conceptual system. Double modality of the representation of high imageable nouns in the mental lexicon, contrasted with single representation in low imageable nouns is argued to facilitate the processing of a concrete noun and slow down successful retrieval, access and any further processing of an abstract noun. The aim of this study is to investigate whether there is a variation in the semantic processing of high and low imageable words in people with aphasia compared to the healthy control speakers when presented with a visual or auditive stimulus. Conducted research was designed to examine the processing of the lexical feature of imageability and hence included four tests from PALPA battery of tests adapted for Croatian: Auditory Synonym Judgement, Written Synonym Judgement and Word Semantic Association. To reduce the effect of perceptive impairments, general semantic processing was verified by conducting two follow-up PALPA comprehension tests: Spoken Word-Picture Matching and Written Word-Picture Matching. The study included 30 aphasic participants and 30 paired healthy participants; all native speakers of Croatian. In line with the predictions, there was a statistically significant difference between experimental and control group; the experimental group further confirmed the predictions by achieving significantly lower results with respect to low imageable words. Difficulties in recognition of low imageable words in aphasics confirm the existing variations in the organization of processing pathways. The main finding of the research demonstrates that the aphasics, especially Broca’s aphasics, have problems when processing complex psycholinguistic tasks, as well as complex structures involved both in the grammatical and conceptual representations.